Understanding the influence of temperature and frequency on the fatigue resistance of bitumen. (16th August 2021) - Rochlani, Mrinali; Canon Falla, Gustavo; Caro, Silvia; Leischner, Sabine; Wellner, Frohmut
Highlights: Stress-controlled bitumen fatigue tests on cylindrical specimens were performed. Tests were performed at different temperature-frequency combinations. Dissipated energy (DE) theory was used to determine the fatigue life of the bitumen. Multiple approaches were proposed to analyse fatigue damage. 15 °C was identified as a frequency-free transition temperature. Abstract: Fatigue performance of bitumen holds great importance in the design and durability of asphalt pavements. However, there are still gaps in knowledge on the influence of specific experimental conditions on the degradation of bitumen under cyclic loading. Stress-controlled fatigue tests at three temperatures (-10 °C, 15 °C and 20 °C) and two loading frequencies (10 Hz and 20 Hz) were performed on cylindrical specimens of a 50/70 grade bitumen, using a recently developed fatigue testing protocol in the Dynamic Shear Rheometer (DSR) equipment. Experimental data were analysed through multiple analysis approaches, including a novel 'failure lines' method that uses the dissipated energy (DE) of the material and the number of cycles to failure ( Nf ). Experimental results corroborated the impact of temperature and frequency testing conditions on the fatigue response of the bitumen. For example, at 200 kPa and 20 °C, the bitumen dissipated 3.07 times more energy at failure at 10 Hz than at 20 Hz; while at 400 kPa and 10 °C, the bitumen only dissipated 1.07 times more energy at 10 Hz than at 20 Hz. Also, depending on the applied stress, the bitumen tested at 10 Hz dissipated between 2.45 and 4.02 times more energy at 20 °C than at 15 °C, and between 4.11 and 6.52 times more energy at 15 °C than at 10 °C. Additionally, 15 °C was identified as a 'frequency-free transition temperature' for this bitumen, as the 'failure lines' at both frequencies overlapped. Finally, a new temperature and frequency independent fatigue representation was identified when analysing the initial DE and N f data.